Die Rolle des jüdischen Sports in der Mainmetropole Frankfurt vor und nach dem 30. Januar 1933 - Peiffer, Lorenz (Aschkenas, 2017)
From the eleventh century onwards the Jewish community in Frankfurt had developed into one of the centres of Jewish life in Europe. In the early 1930s it was the second largest Jewish community in Germany, counting about 31,000 members. With Bar Kochba, Schild, Jüdischer Arbeiter-Sportclub, Jüdischer Turnerbund and Sportverein des Philanthropin five Jewish sport clubs had already been founded before Hitler’s rise to power. But with only 1,000 members they played a minor role in Frankfurt’s sport society. The majority of the Jewish athletes were members of the middle-class sports clubs in Frankfurt. After the exclusion of Jewish members from the middle-class sports clubs the Jewish athletes’ only choice was to join one of the Jewish sports clubs. After fighting to survive until 1933, the Jewish sports club Schild Frankfurt developed into a major sports club within months.